Thermal Performance of a Dimpled Tube Parabolic Trough Solar Collector (PTSC) with SiO2 Nanofluid - M. Arun; Debabrata Barik; K. P. Sridhar; Milon Selvam Dennison (International Journal of Photoenergy)
In this research work, dimple texture tubes and silicon dioxide (SiO2) nanofluid were used to analyze the performance parameters of a solar water heater. For this purpose, SiO2 was mixed with deionized (DI) water using an ultrasonic dispersion device to prepare the nanofluids (SiO2/DI-H2O). The size of the nanoparticle was in the range of 10-15 nm. Different volume concentrations of the nanoparticles in the range of 0.1% to 0.5%, in steps of 0.1%, were chosen to prepare the nanofluids to carry out the experiments. Apart from this, computational fluid dynamics (CFD) tool was used to numerically analyze the parameters affecting the performance of the solar water heater, as well as the fluid flow pattern in the dimple texture tube. During the experiment, the mass flow rate of the base fluid (water) varied in the range of 0.5 kg/min to 3.0 kg/min in steps of 0.5 kg/min. The added advantage of the dimple texture tube design led to an increase in turbulence in the flow pattern, resulting 34.2% increase in the convective heat transfer efficiency compared with the plain tube. Among all experimental modules, SiO2/DI-H2O with a mass flow rate of 2.5 kg/min and 0.3% volume concentration gives overall optimized results in absolute energy absorption, gradient temperature, and efficiency of the solar water heater. The efficiency metrics of the experimental results were compared with the simulation results, and it was in the acceptable range with an overall deviation of ±7.42%.